Biuletyn Informacyjny . no. 25, 1981 - NSZZ "Solidarność" K.Z. Z.A. "Puławy", [ed. Stanisław Dębicki et al.] (NSZZ "Solidarność" w ZA "Puławy", 1981)
Creation and circulation: For trade-union internal use